Pengaruh Kepemimpinan, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Personil Polisi Biro Rena Polda Sumatera Utara - Bayu Lazuardi; Muhammad Ikhsan Harahap (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to analyze the influence of leadership, work motivation and job satisfaction on the performance of North Sumatra Regional Police Rena Bureau Police personnel. This study was conducted to identify factors that contribute to improving the performance of Rena Bureau Police personnel in carrying out their duties. The research results show that leadership has a significant positive influence on the performance of Rena Bureau Police personnel. Work motivation also has a significant positive influence on personnel performance. Apart from that, job satisfaction was also found to have a significant positive influence on personnel performance. Thus, these factors can be considered as the main drivers of improving the performance of Rena Bureau Police personnel. The implication of this research is that the management of the Rena Police Bureau must pay attention to aspects of leadership, work motivation and job satisfaction in an effort to improve the performance of their personnel. Apart from that, this research also provides useful insights for further research in the field of human resource management in law enforcement agencies.